Problematika Pembelajaran Daring Privat Tahsin Alquran di Binaqu Academy - Muhammad Syafiq; Nurul Latifah Inayati (Departement of Mathematics Education, 2023)
Online learning activity is kind of study that can be implemented in all the time, not only in general study but also in Tahsin method. Tahsin online method can be used by any tools, like handphone, laptop and then by application like WhatsApp, Google Meet and Zoom. The aims of this research to describe the problematic of private online learning Tahsin Alquran in Binaqu Academy with purpose for spread the meaning of Alquran and also eradicating Hijaiyyah illiteracy for muslim in Indonesia. Subject of this research is founder and several teachers in Binaqu Academy. This research used qualitative method. Data collection obtained by interview, observation and documentation to get the fact. The result showed that: (a) The problematic of private online learning in Binaqu Academy are regarding internet network connection, because internet network connection be the one of main condition in online learning activity. (b) Then, is also about discipline and responsibility from the students and several teachers.